Sinergi Antara Bank Syariah dan P2P Lending Fintech dalam Meningkatkan Akses Pembiayaan bagi UMKM di Jawa Barat: Analisis Systematic Literature Review (SLR) - Mulyana, Iwan; Maulin, Mery; Burhanudin, Ujang; Amany, Amany (STAI Al Musaddadiyah Garut, 2024)
This study aims to explore and analyze the synergy between Islamic banks and P2P lending fintech in improving accessibility and financing efficiency for MSMEs in West Java. The methodology used is a Systematic Literature Review (SLR), which allows the researcher to identify, assess, and synthesize relevant studies from the past five years. The main findings show that collaboration between Islamic fintech and Islamic banks can significantly enhance financial inclusion through faster and more accessible financing. Blockchain technology is identified as a key factor in improving transparency and security of transactions, although the existing regulations remain a major challenge. The study concludes that a strong synergy between these two entities can support MSME growth, but its successful implementation heavily depends on more adaptive regulatory support. The practical implications of this research include recommendations for regulators to strengthen the legal framework supporting Islamic fintech innovation, while the social implications involve increasing access to more inclusive financial services for MSMEs, which in turn can drive local economic growth. The limitations of this study are related to its regional focus, which is confined to West Java, so the results may not fully apply to a broader context. Keywords: Islamic Fintech; Islamic Banks; P2P Lending; Financial Inclusion; UMKM..